Two new species of Crepidotus (Crepidotaceae) from China - Zhang, Peng; Ge, Yupeng; Bau, Tolgor (Phytotaxa, 2022)
Crepidotus herbaceus and C. ulmicola, found on herbaceous plants and bark, respectively, are described as new species. A remarkably minute, white, tomentose pileus and broadly ellipsoid to ellipsoid, almost smooth or finely ornamented basidiospores distinguish the two species from other members of Crepidotus. The habitats of the two species (on bark of Ulmus trees and on leaves and stems of living herbaceous plants) are unusual in this nearly saprophytic fungal genus. Bayesian Inference (BI) and Maximum Likelihood (ML) analyses based on ITS rDNA confirmed the distinctiveness of these two new species. Full descriptions, scanning electron micrographs of basidiospores, and morphological illustrations are provided.